e-Environment in education: UUM perspective - Abdul Hamid, Mohd Noor; Zaibon, Syamsul Bahrin; Ahmad, Jasni; Wan Ishak, Wan Hussain (2007)
Many universities around the globe have established e learning, whether as a teaching medium or as one of the courses. To support these initiatives and to fulfill elearning agenda, e-learning required support from other “e” domains which is called eenvironment.Different features are available in the e-environment that can be fulfill wholly or partly, e-learning knowledge requirement. E-learning contents which are traditionally published, as printed materials can be very consuming in term of cost and mobility. Hence, e-publishing which is one of the features in e-environment is vital to support e-learning initiatives. This approach may contribute to the implementation of the total e-environment in education. This paper discusses e-publishing model, which aims to capitalize on the features of the Internet and the web technology. Apart from that it also touches on the experiences of the Universiti Utara Malaysia (UUM) in adopting the e-environment in its education.